UTILIZATION OF SMARTPHONE DEVICES AND USE OF SOCIAL MEDIA IN NORTH MALUKU - nfn Bahrawi (Journal of Information Technology and Its Utilization, 2018)
Basic guidelines. This document is itself an example of the desired layout (inclusive of this abstract) and can be used as a template. It contains information regarding desktop publishing format, type sizes, and typefaces. Style rules are provided that explains how to handle equations, units, figures, tables, abbreviations, and acronyms. Sections are also devoted to the preparation of acknowledgments, references, and authors' biographies. The abstract is limited to 150–200 words and cannot contain equations, figures, tables, or references. It should concisely state what was done, how it was done, principal results, and their significance.